Representation Of Teenage Identity On Instagram: Dual Account Practices And Self-Presentation In Digital Society - Sumaiyah Menjamin (Journal of Sumatera Sociological Indicators, 2026)
This study looks at how teenagers create and show their identities on Instagram by using two different accounts, called the first account and the second account. This study uses a quantitative method based on survey data from 28 teenage Instagram users aged 13 to 20, drawing on the idea of the looking-glass self and how people present themselves online. The results show that 82.1% of people have a second account, which they use as a private place to express their true selves. At the same time, their main account is used to show more socially acceptable and positive versions of themselves. This shows the balance people try to keep between how they present themselves online and who they really are in private. The study shows how the features of a platform influence how people build their online identities, emphasizing the importance of choosing what to share and how to target different groups of people. These findings help us better understand how young people develop their identities in the digital world of connected societies. Keyword: Instagram, Digital Sociology, Identity Representation, Teenagers, Self-Presentation